Overview Of Nursing Students' Knowledge About Hypoglycemia - Rachmat Chusnul Choeron; Dudella Desnani Firman Yasin (Care : Jurnal Ilmiah Ilmu Kesehatan, 2025)
Introduction. Hypoglycemia is often found in cases of diabetes mellitus and non-diabetes mellitus. Recognizing the signs and symptoms and proper treatment of hypoglycemia is one of the competencies that must be mastered by nursing students. However, even though students have studied the concept of hypoglycemia, they still have difficulty understanding it. The purpose of this study was to explore nursing students' knowledge of the concept of hypoglycemia. Method. The design of this study was a descriptive design with a target population of 249 nursing students at the Faculty of Health Sciences, Tribhuwana Tunggadewi University. A sample of 91 students was taken using a stratified sampling technique. The variable in this study was knowledge of hypoglycemia which was measured using a questionnaire developed by the researcher. Data were analyzed using descriptive statistics. Results. The results of this study showed that almost all respondents did not know the concept of hypoglycemia (91.2%) even though they had previously studied the concept of hypoglycemia in lectures using lecture methods and PowerPoint presentation. Conclusion. Lecturers need to adjust learning methods and media that are more interesting and effective in achieving learning outcomes based on the characteristics of students.